(untitled) (Medical Forum Monthly, 2021)
Objective: This study was performed to compare the outcome of open and closed lateral internal sphincterotomy in terms of early postoperative complications. Study Design: Quasi-experimental study Place and Duration of Study: This study was conducted at the Department of Surgery, Liaquat University of Medical & Health Sciences, Jamshoro Pakistan from June 2017 to May 2018. Materials and Methods: All the patients with chronic anal fissure were consented and enrolled in the study. After lateral internal anal sphincterotomy, either by open or closed technique, outcomes were recorded on a pre-approved Performa. Data regarding patient’s demographic characteristic age, gender and pain, bleeding, infection, soiling of clothes) was recorded. Results: A total of 50 patients underwent closed anal sphincterotomy (11 males; mean age, 34.9 years) and 50 patients had open anal sphincterotomy (12 males; mean age, 27.77 years). There was a significant difference in infection rates between open and closed internal sphincterotomy (4.4% & 15.6%; p-value =0.013). The postoperative pain and bleeding were statistically insignificant in both groups (p=0.145).Postoperative hospital stay was found to be significant (p-value = <0.001) and mean shorter hospital stay in patients undergoing closed anal sphincterotomy. Conclusion: Closed and open Lateral internal sphincterotomy is effective in the treatment of chronic anal fissure. Close internal sphincterotomy is preferable to open internal sphincterotomy because it affects a similar rate of postoperative pain, bleeding, and fewer hospital stay days.